2008
DOI: 10.1186/1755-8794-1-54
|View full text |Cite
|
Sign up to set email alerts
|

The distinctive gastric fluid proteome in gastric cancer reveals a multi-biomarker diagnostic profile

Abstract: Background: Overall gastric cancer survival remains poor mainly because there are no reliable methods for identifying highly curable early stage disease. Multi-protein profiling of gastric fluids, obtained from the anatomic site of pathology, could reveal diagnostic proteomic fingerprints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 60 publications
1
39
0
Order By: Relevance
“…Finally, they concluded that the tissue expression of PGC may represent a powerful tool for the diagnosis of prostate cancer. Another report showed that the PGC is among prominent down-regulated markers in the gastric cancer (Kon et al, 2008). At present, there are many reports in support of the biological importance and proteomic signature of PGC as a biomarker for gastric carcinoma (Melle et al, 2005;Kon et al, 2008).…”
Section: Pgc As a Biomarkermentioning
confidence: 98%
See 2 more Smart Citations
“…Finally, they concluded that the tissue expression of PGC may represent a powerful tool for the diagnosis of prostate cancer. Another report showed that the PGC is among prominent down-regulated markers in the gastric cancer (Kon et al, 2008). At present, there are many reports in support of the biological importance and proteomic signature of PGC as a biomarker for gastric carcinoma (Melle et al, 2005;Kon et al, 2008).…”
Section: Pgc As a Biomarkermentioning
confidence: 98%
“…Another report showed that the PGC is among prominent down-regulated markers in the gastric cancer (Kon et al, 2008). At present, there are many reports in support of the biological importance and proteomic signature of PGC as a biomarker for gastric carcinoma (Melle et al, 2005;Kon et al, 2008). Chae et al (2008) have recently studied the clinical utility of serum pepsinogen levels as a screening test of atrophic gastritis.…”
Section: Pgc As a Biomarkermentioning
confidence: 99%
See 1 more Smart Citation
“…2. The gastric fluid protein profiles between patients with gastric disease and healthy individuals have been compared using various techniques, such as ProteinChip arrays with copper (II) IMAC3, weak cation exchange (WCX2 and CM10), strong anion exchange (SAX2), and hydrophobic interaction (H50) [35]. In a recent study, clinical gastroscopy, 2-DE, and MS analysis were applied to achieve distinct gastric fluid protein profiles.…”
Section: Gastric Fluidmentioning
confidence: 99%
“…However, the presence of specific gastric fluid biomarkers can further aid in the evaluation of symptomatic patients, thus leading to a definitive diagnosis. Of particular importance are pepsin-related proteins such as pepsinogen C [35], pepsin A [35], α1-antitrypsin [36], and pepsinogen II [37] that have been shown to have altered expressions in gastric cancer. These findings suggest that the activation of proteolytic enzymes in gastric fluid may play an important factor in gastric carcinogenesis.…”
Section: Gastric Fluidmentioning
confidence: 99%